A rare face of follicular lymphoma: reverse variant of follicular lymphoma - Ninu Maskey; Qiongrong Chen; Fang Liu; Shangqin Liu; Sufang Tian (BMC, 2020)
Abstract Background Reverse Variant of Follicular Lymphoma (RVFL) is one of the rare morphological variants of FL, characterized by dark staining small centrocytes in the center and pale staining large centroblasts at the periphery of the neoplastic follicles. Only rare cases of RVFL have been described to date. The histological appearance of this little known variant of FL may be misinterpreted if pathologists are unaware of its existence. The main purpose of this study is to draw pathologists' attention to such an uncommon growth pattern of FL so that this variant can be correctly recognized and the clinical significance further studied in the future. Methods Four cases of FL with unusual morphologic features were evaluated for the expression pattern of CD20, CD10, BCL6, BCL2, CD21, CD23, CD3, CD5, Cyclin D1, IgD and Ki67 by immunohistochemistry. Fluorescence in situ hybridization (FISH) with break-apart probes was performed to detect BCL2 gene rearrangement. Results All four cases showed distinctive morphologic pattern of RVFL; in addition, each also exemplified unique morphological features. Immunohistochemical stains confirmed the cells in both the central areas and the peripheral cuffs had the same immunophenotypic profiles, contrasting to the FL with marginal zone differentiation in which only the center of the nodules showed expression of CD10. FISH demonstrated BCL2 gene rearrangement in all cases. Conclusion The growth pattern of this rare FL variant may mimic FL with marginal-zone differentiation and other entities including but not limited to marginal zone lymphoma (MZL), progressive transformation of germinal centers (PTGC) and nodular lymphocyte predominant Hodgkin lymphoma (NLPHL). Pathologists should be familiar with this unusual morphological variant to avoid diagnostic pitfalls.